Design of a hardware track finder (Fast Tracker) for the ATLAS trigger - Cavaliere, Viviana; Klimkovich, Tatsiana; Kolb, Mathis; Schöning, André; Soltveit, Hans Kristian (Journal of Instrumentation, 2016)
The use of tracking information at the trigger level in the LHC Run II period is crucial for the trigger and data acquisition system and will be even more so as contemporary collisions that occur at every bunch crossing will increase in Run III. The Fast TracKer is part of the ATLAS trigger upgrade project; it is a hardware processor that will provide every Level-1 accepted event (100 kHz) and within 100μs, full tracking information for tracks with momentum as low as 1 GeV . Providing fast, extensive access to tracking information, with resolution comparable to the offline reconstruction, FTK will help in precise detection of the primary and secondary vertices to ensure robust selections and improve the trigger performance.
Gesehen am 29.04.2020